Employers' Associations, Worker Mobility, and Training - Pedro S. Martins; Jonathan P. Thomas (Global Labor Organization (GLO), 2023)
This paper studies firm-provided training in a context of potential worker mobility. We argue that such worker mobility may be reduced by employers' associations (EAs) through no-poach agreements. First, we sketch a simple model to illustrate the impact of employer coordination on training. We then present supporting evidence from rich matched panel data, including firms' EA affiliation and workers' individual training levels. We find that workers' mobility between firms in the same EA is considerably lower than mobility between equivalent firms not in the same EA. We also find that training provision by EA firms is considerably higher, even when drawing on within-employee variation and considering multiple dimensions of training. We argue that these results are consistent with a role played by EAs in reducing worker mobility.
Keywords: J53; J62; L40; 330; Employers organisations; No-poach agreements; Worker mobility